Living traditions - Glassie, Henry; Mahmud, Firoz (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; translated from Bengali; chiefly on the handicrafts and traditional arts of Bangladesh.
Includes bibliographical references and index.
Keywords: Culture; Sociology